2019
DOI: 10.1186/s13256-019-2188-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug-induced psychosis associated with MTHFR C677T: a case report

Abstract: Background Various antiepileptic drugs can potentially cause psychiatric side effects in patients with epilepsy, but the precise mechanism of these actions remains unknown. In recent years, the common polymorphism C677T in the 5,10-methylenetetrahydrofolate reductase ( MTHFR ) gene has attracted attention for its role in the onset of psychiatric diseases. MTHFR and several vitamins (as cofactors) are crucial for remethylation of homocysteine via folate and homocysteine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This study indicated that epilepsy occurs in about half of patients with adolescent/adult-onset MTHFR deficiency, and these patients have a highly variable response to antiepileptic drugs (AEDs) [27]. A few cases have also documented MTHFR deficiency, such as in a 14-year-old girl with progressive myoclonic epilepsy [28] and in AED-induced psychosis [29].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that epilepsy occurs in about half of patients with adolescent/adult-onset MTHFR deficiency, and these patients have a highly variable response to antiepileptic drugs (AEDs) [27]. A few cases have also documented MTHFR deficiency, such as in a 14-year-old girl with progressive myoclonic epilepsy [28] and in AED-induced psychosis [29].…”
Section: Introductionmentioning
confidence: 99%